Investigation of the use of wet ethanol in an HCCI engine using water injection and direct exhaust heat recovery - G.D. Telli; G.Y. Zulian; T.D.M. Lanzanova; M.E.S. Martins; L.A.O. Rocha (Energy Conversion and Management: X, 2023)
Wet ethanol is a renewable fuel that has great potential to reduce the energy cost of ethanol production and improve the life-cycle carbon footprint of ethanol. The use of wet ethanol in homogeneous charge compression ignition (HCCI) mode can achieve high efficiency with low emission levels. In this context, this study investigates the effects of water-in-ethanol concentration on the performance, emissions, and combustion characteristics of an HCCI engine using water injection and recirculation of all exhaust gasses from a diesel cylinder. Water injection was used to solve the problem that there is no direct method to adjust HCCI combustion. Results showed that water–ethanol blends with higher water content had lower heat release rates and combustion temperatures, which increased the combustion duration. The indicated efficiency deteriorated for ethanol–water blends with high water concentrations. However, the highest indicated efficiency was 39.3% for the blend with 20% water by vol. at 6.0 bar. CO and organic gas emissions tended to increase with late combustion and for blends with higher water content, reaching values of 78.0 and 68.2 g/kWh at 4.0 bar, respectively. On the other hand, the NOX emissions were low, reaching a maximum value of 0.93 g/kWh in the HCCI combustion.